Enhanced wound healing via ROS-triggered release of ascorbyl tetraisopalmitate loaded in ferrocene-based polymer nanoparticles - Sohyeon Yu; Minhyeok Lee; Dongseong Seo; Hyungjun Kim; Chan-Su Park; Daekyung Sung (Redox Biology)
Ascorbyl tetraisopalmitate (AT), a vitamin C derivative, exhibits better stability and transdermal absorption than vitamin C and shows potential for skin whitening and wound healing. However, their low water solubility and specific storage requirements limit their application. To overcome these limitations, in this study, we aimed to develop AT-loaded ferrocene polymer nanoparticles (AT@FNPs) using biocompatible amphiphilic polymers. The nanoprecipitated nanoparticles exhibited enhanced AT stability, loading efficiency, and controlled release in reactive oxygen species (ROS)-rich wound environments. Moreover, the ROS ROS-trigger of AT@FNPs facilitated targeted drug release and ROS scavenging, thereby enhancing the antioxidant activity. The release of AT from the AT@FNPs in wounds promoted cell proliferation and accelerated wound closure in a mouse model. Overall, our findings highlight the potential of the developed ROS-triggered AT@FNPs as smart drug delivery systems for wound healing and skin treatment.